2009
DOI: 10.5539/gjhs.v1n1p27
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Analyzing Hospital Length of Stay with Application to Inpatients Dying in Southern Thailand

Abstract: This study investigated length of stay (LOS) for patients who died in hospital in Southern Thailand from 2000 to 2003 with respect to principal diagnosis and demographic, geographic and hospital size factors. The computerized data of 40,498 mortality cases were obtained from the Ministry of Public Health from 167 hospitals in 14 provinces of Southern Thailand between October 2000 and September 2003 with information on age, gender, principal diagnosis, province and hospital size. Logistic and linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The reason for increased LOS along with age could be the presence of chronic disease in older ages, which required a longer hospital stay. A Lim study in south Thailand showed that age affected LOS, and with increasing age LOS increases as well (17). The current study results indicated that marital status affects LOS, and married patients had longer stays than bachelors, which is similar to the results of other studies (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for increased LOS along with age could be the presence of chronic disease in older ages, which required a longer hospital stay. A Lim study in south Thailand showed that age affected LOS, and with increasing age LOS increases as well (17). The current study results indicated that marital status affects LOS, and married patients had longer stays than bachelors, which is similar to the results of other studies (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…They claimed that stroke severity is an important predictor of both acute and total LOS. Some studies have reported that patient demographics and hospital attributes were the two major factors that contributed to identifying patient LOS [3], and the most useful patient feature for predicting LOS was patient's age [32]. In many studies, age has been found to be a very significant predictor of LOS [5].…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable interest in controlling hospital costs, particularly in cardiac diseases; thus, hospitals try to make LOS as short as possible [2]. The length of hospital stay is an actual parameter applied to identify health care resource utilization, health cost, and severity of illness [3]. The use of LOS is highly predictive of inpatient costs as a marker of resource utilization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first model, we assume X as a random variable denoting LoS, which follows a log-normal distribution with parameters l and r. The parameter r is the shape parameter of X, while e l is the scale parameter of X, where X!1. It has been widely known that distribution of LoS is rightly skewed (Atienza, 2005;Atienza, Garc ıa-Heras, Muñoz-Pichardo, & Villa, 2008;Hellervik & Rodgers, 2007;Lim & Tongkumchum, 2009) and empirical evidence for log-normal distribution for LoS in a hospital is provided by Marazzi et al (1998). In the second model, we assume that the LoS follows an Erlang-K distribution with scale parameter k and shape parameter h.…”
Section: Flat Rate Pricing Modeltheory Developmentmentioning
confidence: 99%